Induction of chromosome aberrations in the Allium cepa test system caused by the exposure of seeds to industrial effluents contaminated with azo dyes - Caritá, R. [UNESP]; Marin-Morales, M. A. [UNESP] (Elsevier, 2008)
Numerous potentially mutagenic chemicals have been studied mainly because they can cause damaging and inheritable changes in the genetic material. Several tests are commonly used for biomonitoring pollution levels and to evaluate the effects of toxic and mutagenic agents present in the natural environment. This study aimed at assessing the potential of a textile effluent contaminated with azo dyes to induce chromosomal and nuclear aberrations in Allium cepa test systems. A continuous exposure of seeds in samples of the textile effluent in different concentrations was carried out (0.3%, 3%, 10%, and 100%). Cells in interphase and undergoing division were examined to assess the presence of chromosome aberrations, nuclear changes, and micronuclei. Our results revealed a mutagenic effect of the effluent at concentrations of 10% and 100%. At lower concentrations, the effluent (3% and 0.3%) did not induce mutagenic alterations in the test organism A. cepa. These findings are of concern, since cell damage may be transmitted to subsequent generations, possibly affecting the organism as a whole, as well as the local biota exposed to the effluent discharge. If the damage results in cell death, the development of the organism may be affected, which could also lead to its death. © 2008 Elsevier Ltd. All rights reserved.
Keywords: Allium cepa; Azo dye; Chromosome aberrations; Cristais River; Micronuclei; Mutagenicity; Azo dyes; Chromosomes; Concentration (process); Toxic materials; Effluents; azo dye; industrial effluent; biomonitoring; chromosome; dye; effluent; industrial emission; mutagenicity; pollution effect; pollution exposure; seed; textile industry; vegetable; cell damage; cell division; chromosome aberration; controlled study; cytotoxicity; interphase; micronucleus; nonhuman; onion; plant seed; Azo Compounds; Brazil; Cell Nucleus; Cell Survival; Chromosome Aberrations; Coloring Agents; Environmental Monitoring; Industrial Waste; Micronucleus Tests; Onions; Seeds; Textile Industry; Water Pollutants, Chemical; Water Pollution, Chemical